Journalism Transformation: Print Media Towards the Digitalization Era for Generation X - Djudjur Luciana Rajagukguk (IJESS International Journal of Education and Social Science, 2022)
Print media has advantages that do not exist in online media in the form of ease of reading anywhere without having to access the internet. The depth of print media in writing news in more detail, not with online media which prioritizes the speed of news presentation. The presence of technology for generation X is actually an extraordinary thing, but it also demands to have to master technology that is experiencing accelerated technological progress. The most significant characteristic difference in generation X with other generations is the mastery of information and technology. The purpose of this study was to identify and analyze the transformation of journalism: print media into the digitalization era for generation X. The research method used was descriptive qualitative, all facts and social phenomena, and field observations were carried out and then analyzed based on what was observed. Data analysis in qualitative research is carried out simultaneously with the data collection process. Qualitative data analysis begins with analysis as data that researchers have collected in the field. The data is good through literature study. The results of the study describe the transformation of journalism: print media towards the era of digitization in generation X provides faster things, but for the generation they still have doubts about their abilities. It requires a deeper form of trust in print media, so that with the advent of digital media, it is hoped that the content of news and information will be the same. That what is written in print media can be read in the world of digital media with just the touch of a finger.